The application of a phycocyanin extract obtained from Arthrospira platensis as a blue natural colorant in beverages - García, Ana Belén; Longo, Eleonora; Bermejo, Ruperto (Journal of applied phycology, 2021)
Currently, the food additive industry has interest in replacing artificial dyes with natural pigments, trying to maintain consumer interest and increase their awareness towards healthy diets. Phycobiliproteins are light-harvesting and water-soluble proteins extracted from cyanobacteria and red algae that can be employed as natural additives. In the present work, a C-phycocyanin extract from the cyanobacterium Arthrospira platensis was tested as blue colorant in beverages to demonstrate that samples containing the protein extract have a color similar to marketed beverages containing synthetic dyes. Using spectroscopy and colorimetry, the extract was characterized and gave evidence of having good properties and good stability in the pH range between 3.0 and 9.0. The staining factors, representing the amount of blue protein needed to reproduce the color of bluish commercial samples, ranged between 15.6 and 111.7 mg·L −1 , being sufficiently low in all samples. Additionally, color stability during a short period of cold storage was studied: it demonstrated that isotonic and tonic beverages remained stable throughout the 11-days analysis period with no significant changes. These results prove that the C-phycocyanin extract has potential applications in food as natural colorant, being an alternative option to synthetic coloring molecules.